Co-producción de conocimiento a través de imágenes (Fotovoz) sobre los procesos de identificación/diferenciación de jóvenes hijos(as) de migrantes nacidos y/o escolarizados en Chile (Polis (Santiago), 2024)
With this article we propose to contribute to the field of participatory and collaborative methodologies in social sciences, from the experiences with photovoice in Latin America. , from  the investigation of the processes of identification and ethno-national belongings of the young children of migrants (born and/or schooled in Chile). We propose to conceive photovoice as a device for co-construction of knowledge of young people, showing the way in which it opens up space for the production of emerging knowledge that does not correspond only to what is already known. And also  as a device for the production of group reflections in which youths have a place, no longer merely as participants but as collaborators too, in the analysis of the photographs produced by them in the inquiry process itself.
Keywords: Qualitative methodologies, participatory methodologies, photovoice, migrant’s youths